2020
DOI: 10.1126/science.aba2658
|View full text |Cite
|
Sign up to set email alerts
|

The malaria parasite has an intrinsic clock

Abstract: Malarial rhythmic fevers are the consequence of the synchronous bursting of red blood cells (RBCs) on completion of the malaria parasite asexual cell cycle. Here, we hypothesized that an intrinsic clock in the parasite Plasmodium chabaudi underlies the 24-hour-based rhythms of RBC bursting in mice. We show that parasite rhythms are flexible and lengthen to match the rhythms of hosts with long circadian periods. We also show that malaria rhythms persist even when host food intake is evenly spread across 24 hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
115
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(122 citation statements)
references
References 64 publications
7
115
0
Order By: Relevance
“…Our results suggest that a product of food digestion schedules the IDC, supporting those of Prior et al [19] and Hirako et al [18], yet-at first glance-apparently contradicting two experiments, relating to food intake and infection of TTFLclock disrupted mice, respectively, in Rijo-Ferreira et al [10]. First, the food intake experiment in Rijo-Ferreira et al [10] aimed to test if the act of eating itself schedules the IDC. They infected WT mice housed in LD cycles, thus despite food provision being spread evenly throughout the day and night, these hosts retained their nocturnal lifestyle, including undergoing the bulk of metabolism at night.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…Our results suggest that a product of food digestion schedules the IDC, supporting those of Prior et al [19] and Hirako et al [18], yet-at first glance-apparently contradicting two experiments, relating to food intake and infection of TTFLclock disrupted mice, respectively, in Rijo-Ferreira et al [10]. First, the food intake experiment in Rijo-Ferreira et al [10] aimed to test if the act of eating itself schedules the IDC. They infected WT mice housed in LD cycles, thus despite food provision being spread evenly throughout the day and night, these hosts retained their nocturnal lifestyle, including undergoing the bulk of metabolism at night.…”
Section: Discussionsupporting
confidence: 56%
“…Second, like our design, Rijo-Ferreira et al [10] gave TTFL-clock disrupted mice (Cry1/Cry2 null) food ad libitum and housed them in constant darkness, yet they found IDC rhythms (in infections started with synchronous parasites) remained strong. Rijo-Ferreira et al's [10] mice were kept in LD cycles until the point of infection which may allow residual rhythms generated by masking to persist for the first few days of infection. Indeed, when these TTFLclock disrupted hosts are housed in constant darkness for a week before infection, IDC rhythms do become dampened ( fig.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Rijo-Ferreira et al 40 evaluated the impact of different factors in parasite rhythms by analyzing the transcriptome of rodent Plasmodium chabaudi parasites. They showed that parasites present a group of genes with rhythmic expression sustained in the absence of light, implying that parasites possess an intrinsic clock, and the host is not the only one to drive their cell cycle length.…”
Section: Discussionmentioning
confidence: 99%